PCR based method for authentication of pork in raw and processed products as well as in binary meat mixtures - R THOMAS; M SAIKIA; S SINGHA; Z BARUAH; R KALITA; N SAHARIA; S RAJKHOWA (Indian Journal of Animal Sciences, 2021)
In this study, amplification of species-specific marker of mitochondrial DNA origin was carried out to detect pork in raw, processed and meat mixtures containing varying concentrations of pork, viz. 1, 10, 50, 75 and 100%. The species-specific marker for pork was tested in raw pork from different breeds/varieties of pig such as Hampshire, Yorkshire, Ghungroo, Duroc, Rani, and Asha. The size of the amplified product was 290 bp in all the breeds/ varieties. The results were consistent in processed pork products, viz. frankfurter sausage, salami, cocktail sausage, pork slice, ham, and pork curry which were subjected to different cooking temperatures ranging from 75 to 121Â°C. In case of all the mixtures with different concentrations of pork, similar results were observed. Subsequently, this marker was tested for cross-amplification by checking them with beef, carabeef, mutton, chevon, chicken, and duck meat and no amplification was observed. The results suggested that the DNA marker used in this study is highly species-specific and reliable to detect pork adulteration, unambiguously, in raw, processed as well as in meat mixtures containing pork. This technique is rapid, simple and economical as compared to other methods of pork adulteration detection.